2012
DOI: 10.1029/2012gc004341
|View full text |Cite
|
Sign up to set email alerts
|

Constraining volcanic inflation at Three Sisters Volcanic Field in Oregon, USA, through microgravity and deformation modeling

Abstract: [1] Microgravity data were collected between 2002 and 2009 at the Three Sisters Volcanic Complex, Oregon, to investigate the causes of an ongoing deformation event west of South Sister volcano. Three different conceptual models have been proposed as the causal mechanism for the deformation event:(1) hydraulic uplift due to continual injection of magma at depth, (2) pressurization of hydrothermal systems and (3) viscoelastic response to an initial pressurization at depth. The gravitational effect of continual m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…The largest daily closures occurred when surveying over jungle paths, dirt roads, and large changes in elevation where the gravimeter was subject to vibration and opportunities to repeat base station measurements were limited. The travel‐induced data tares are the most probable cause for the large closure errors observed [e.g., Crider et al , ; Zurek et al , ]. Data reduction included terrain corrections, bathymetry, free air correction, removal of solid Earth tides, Earth curvature, and removal of the regional field.…”
Section: Data Reduction and Residual Gravity Fieldmentioning
confidence: 99%
“…The largest daily closures occurred when surveying over jungle paths, dirt roads, and large changes in elevation where the gravimeter was subject to vibration and opportunities to repeat base station measurements were limited. The travel‐induced data tares are the most probable cause for the large closure errors observed [e.g., Crider et al , ; Zurek et al , ]. Data reduction included terrain corrections, bathymetry, free air correction, removal of solid Earth tides, Earth curvature, and removal of the regional field.…”
Section: Data Reduction and Residual Gravity Fieldmentioning
confidence: 99%
“…Zurek et al. (2012) reported results of such measurements made between 2002 and 2009. Their modeling predicted a 20–30 µGal gravity increase at the center of uplift during that period if the observed surface deformation were caused by magma intrusion.…”
Section: Discussionmentioning
confidence: 99%
“…This is compatible with the formation of viscoelastic aureoles as a result of the alteration of the mineralogical and rheological properties of the surrounding rocks. Previously, Zurek et al (2012) concluded, based on the lack of gravity change from [2002][2003][2004][2005][2006][2007][2008][2009], that deformation at Three Sisters reflects a viscoelastic response of the crust to an intrusion of magma. The estimated e-folding indicates viscosities of ∼10 18 Pa s of a viscoelastic shell surrounding the magmatic source with a pressure change which increases in finite time from 0 to a constant value, considering theoretical estimations on the time constants and viscoelastic medium parameters (e.g., Newman et al, 2001;Bonafede and Ferrari, 2009;Del Negro et al, 2009;Segall, 2016).…”
Section: Time-scales Of Inter-eruptive Uplift Signals: Three Sisters and Other Volcanoesmentioning
confidence: 99%
“…Interpretation of the temporal evolution of InSAR, leveling and GPS data suggests the beginning of deformation in late 1997 or 1998, with a maximum uplifting rate of 3-5 cm/year during 1998. Microgravity data collected between 2002 show no significant change in the mass flux across the deforming area (Zurek et al, 2012). No studies have been published about the uplift evolution over the last decade.…”
Section: Introductionmentioning
confidence: 98%